Subdural Hematoma: An Adverse Event of Electroconvulsive Therapy—Case Report and Literature Review - Ranganath R. Kulkarni; Sateesh Melkundi (Case Reports in Psychiatry)
Electroconvulsive therapy (ECT) is commonly used in the management of medication nonresponsive depressive disorder, with proven efficacy in psychiatric practice since many decades. A rare complication of intracranial bleed following this therapeutic procedure has been reported in sporadic case reports in the English literature. We report a case of such a complication in a 42-year-old male, a known case of nonorganic medication nonresponsive depressive disorder for the last two years who required ECT application. Presenting symptoms included altered mental state, urinary incontinence, and repeated episodes of vomiting; following ECT procedure with magnetic resonance imaging (MRI) of the brain suggestive of bilateral acute subdural hematoma. Despite the view that it may be used in neurological conditions without raised intracranial tension, it will be worthwhile to be vigilant during post-ECT recovery for any emergent complications.